Association of postmigration stressors and intolerance of uncertainty to posttraumatic stress disorder in asylum seekers: the moderating role of environmental sensitivity - Moscardino, Ughetta; Ceccon, Chiara; Mastromatteo, Libera Ylenia; Scrimin, Sara; Lionetti, Francesca; Pluess, Michael (Frontiers in Psychology, 2025)
IntroductionAsylum seekers are frequently exposed to severe pre- and postmigration stressors that place them at elevated risk for posttraumatic stress disorder (PTSD). While much is known about trauma exposure, less research has examined how individual differences in environmental sensitivity—defined as heightened responsiveness to contextual influences—shape mental health outcomes in this population. This study explores how postmigration living difficulties and intolerance of uncertainty relate to specific PTSD symptom clusters, and whether environmental sensitivity moderates these associations.MethodsParticipants were 157 male asylum seekers (Mage = 26.3 yrs, SD = 6.05) mostly originating from West Africa (89%) and hosted in second-line facilities in Northeastern Italy. Asylum seekers were individually interviewed by trained researchers using questionnaires on postmigration living difficulties, intolerance of uncertainty, environmental sensitivity, and posttraumatic stress symptoms.ResultsCommonly reported stressors were lack of work (83%), family separation (77%), fear of deportation (72%), and delays in asylum processing (69%). Overall, 41% of participants exceeded the clinical cutoff for PTSD. Bivariate analyses indicated that postmigration stressors and intolerance of uncertainty were both associated with greater negative cognitions/affect and hyperarousal; postmigration stressors were also related to increased intrusion. In regression models, environmental sensitivity moderated these effects: among individuals facing high postmigration stressors, those low in sensitivity reported fewer avoidance symptoms. Conversely, among individuals with high intolerance of uncertainty, those with average or high sensitivity reported more negative cognitions/affect than their less sensitive peers.DiscussionPostmigration stressors and uncertainty contribute uniquely to PTSD symptomatology among asylum seekers, with environmental sensitivity shaping how these risk factors manifest. Environmental sensitivity-informed interventions (e.g., emotion regulation support for highly sensitive individuals) and policies aimed at reducing uncertainty and structural barriers could help buffer psychological distress in this vulnerable population.